2003
DOI: 10.1073/pnas.1533295100
|View full text |Cite
|
Sign up to set email alerts
|

The p53-dependent effects of macrophage migration inhibitory factor revealed by gene targeting

Abstract: Macrophage migration inhibitory factor (MIF) iscarcinogenesis ͉ cytokines ͉ p21 ͉ transformation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
288
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 265 publications
(297 citation statements)
references
References 70 publications
7
288
2
Order By: Relevance
“…17,18,23 The data presented here implicate E2Fs in mediating this MIF-p53 connection. As we recently showed, loss of MIF augments Rb-mediated repression of E2F responsive genes and reduces the capacity for E2Fs to activate DNA replication, thereby impairing proliferation.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…17,18,23 The data presented here implicate E2Fs in mediating this MIF-p53 connection. As we recently showed, loss of MIF augments Rb-mediated repression of E2F responsive genes and reduces the capacity for E2Fs to activate DNA replication, thereby impairing proliferation.…”
Section: Discussionmentioning
confidence: 53%
“…17 We previously showed that primary fibroblasts derived from MIF-deficient mice exhibit E2F-and p53-dependent growth defects and reduced susceptibility to oncogenic transformation. [23][24][25] Concurrent deletion of the p53 gene reversed the observed phenotype of cells deficient in MIF, providing the first genetic evidence for a functional link between MIF and the p53 tumor suppressor. 23 Here, we provide direct evidence for the tumor-promoting role of MIF in vivo.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations